Chemical Interrogation of Drug/RNA Complexes: From Chemical Reactivity to Drug Design1. Issue 11 (7th February 2013) - Jiménez‐Moreno, Ester; Gómez‐Pinto, Irene; Corzana, Francisco; Santana, Andrés G.; Revuelta, Julia; Bastida, Agatha; Jiménez‐Barbero, Jesus; González, Carlos; Asensio, Juan Luis
<x xml:space="preserve">Abstract</x> When you're in a (RNA) bind: An NMR‐based method to explore the reactivity of ligand/RNA complexes can be used as source of valuable information for drug design. By combining NMR spectroscopy and a simple isotopic labeling strategy (see picture), positional chemical reactivity information can be readily extracted from complex aminoglycoside mixtures. C green, N blue, O red, Me purple.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>